2022
DOI: 10.1101/2022.03.07.483280
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lhx2 in germ cells suppresses endothelial cell migration in the developing ovary

Abstract: LIM-homeobox genes play multiple roles in developmental processes, but their roles in gonad development are not completely understood. Herein, we report that Lhx2, Ils2, Lmx1a, and Lmx1b are expressed in a sexually dimorphic manner in mouse, rat, and human gonads during sex determination. Amongst these, Lhx2 has female biased expression in the developing gonads of species with environmental and genetic modes of sex determination. Single-cell RNAseq analysis revealed that Lhx2 is exclusively expressed in the ge… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Our results revealed that amongst the LIM-HD genes, expression of Lhx2 is sexually dimorphic with higher levels in the female gonads during sex determination in multiple species. We further observed that loss of Lhx2 in the XX mouse gonads leads to ectopic migration of the endothelial cells without causing somatic cell sex reversal [66].…”
Section: Introductionmentioning
confidence: 62%
“…Our results revealed that amongst the LIM-HD genes, expression of Lhx2 is sexually dimorphic with higher levels in the female gonads during sex determination in multiple species. We further observed that loss of Lhx2 in the XX mouse gonads leads to ectopic migration of the endothelial cells without causing somatic cell sex reversal [66].…”
Section: Introductionmentioning
confidence: 62%
“…Beyond granulosa cells, the functions of other ovarian cell populations such as NR2F2+ interstitium or germ cells cannot be ignored. For instance, Lhx2 gene in germ cells is involved in repression of endothelial cell migration in the mouse developing ovary (Singh et al, 2022).…”
Section: Discussionmentioning
confidence: 99%